CGRP blockade by galcanezumab was not associated with reductions in signs and symptoms of knee osteoarthritis in a randomized clinical trial. Issue 12 (December 2018) - Jin, Y.; Smith, C.; Monteith, D.; Brown, R.; Camporeale, A.; McNearney, T.A.; Deeg, M.A.; Raddad, E.; Xiao, N.; de la Peña, A.; Kivitz, A.J.; Schnitzer, T.J.
Summary: Objective: This study tested whether galcanezumab, a humanized monoclonal antibody with efficacy against migraine, was superior to placebo for the treatment of mild or moderate osteoarthritis (OA) knee pain. Method: In a multicenter, double-blind, placebo- and celecoxib-controlled trial, patients with moderate to severe OA pain were randomized to placebo; celecoxib 200 mg daily for 16 weeks; or galcanezumab 5, 50, 120, and 300 mg subcutaneously every 4 weeks, twice. The primary outcome was change from baseline at Week 8 in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscore measured by 100 mm visual analog scale (VAS). The trial was considered positive if ≥1 dose of galcanezumab demonstrated ≥95% Bayesian posterior probability of superiority to placebo and ≥50% posterior probability of superiority to placebo by ≥9 mm. A planned interim analysis allowed termination of the study if posterior probability of superiority to placebo by ≥9 mm was ≤5%. Secondary endpoints included WOMAC function subscore and Patient Global Assessment (PGA) of OA. Safety and tolerability were also assessed. Results: The study was terminated after interim analysis suggested inadequate efficacy. Celecoxib significantly reduced WOMAC pain subscore compared with placebo [−12.0 mm; 95% confidence interval (CI) −23 to −2 mm]. None of the galcanezumab arms demonstrated clinically meaningful improvement (range: 1.5 to −5.0 mm) or met the prespecified success criteria. No improvement in any secondary objective was observed. Galcanezumab was well tolerated by OA patients. Conclusions: This study failed to demonstrate sufficient statistical evidence that galcanezumab was efficacious for treating OA knee pain. Study identification: NCT02192190 .